Meningkatkan Kualitas Desain Pembelajaran Berorientasi Proyek Melalui Penilaian Formatif dan Sumatif yang Terintegrasi - Nurhikmah; Musdalifa; Namirah, Alya (Inspirasi : Jurnal Pendidikan dan Kebudayaan, 2025)
Project-oriented learning design is an effective pedagogical approach in increasing student involvement and developing critical thinking and problem solving skills. The research method used is library research, which involves collecting information from various sources such as books, notes, magazines, and related articles. Data collection techniques are carried out by reading, reviewing and analyzing various existing literature. The data analysis technique used is content analysis. This article discusses the importance of integrating formative and summative assessments in project-oriented learning design to improve the quality and effectiveness of learning. Formative assessment, which functions as continuous feedback, allows educators to monitor and improve the learning process in real-time. Meanwhile, summative assessment provides a comprehensive evaluation of student learning outcomes. The results show that this strategy not only increases student engagement but also significantly improves learning outcomes. Thus, this article suggests that educators need to adopt an integrated assessment approach to achieve higher quality and effective learning design.